Quantification of major saponins in Panax vietnamensis by HPLC-PDA via quantitative analysis of multicomponent by a single marker - Duyen, Ngo Thi My; Kha, Tran Mong; Huy, Nguyen Truong; Long, Vu Huynh Kim (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Panax vietnamensis (Vietnamese ginseng) is an endemic medicinal plant that contains high levels of ocotillol-type saponins, mainly majonoside R2. The quality of this plant is important for its medicinal use and product development. However, conventional quantification methods that use several reference standards are expensive for routine analysis. Objectives: This study aimed to develop a simple method for the quantitative analysis of multiple saponins using ginsenoside Rb1 as a single reference standard, and to evaluate the accuracy of this new method by comparing it with the external standard method (ESM). Subjects and methods: The quantitative analysis of multi-components by a single marker (QAMS) method was used to quantify four ginsenosides (G-Rb1, G-Rd, G-Rg1, and M-R2) with G-Rb1 as a single reference standard. Relative conversion factors (Fi) and relative retention times (RRT) were applied, and differences between QAMS and ESM results were compared using %SMD. Results: The slope-based Fi values (n = 3) were 1.000 (G-Rb1), 1.087 (G-Rd), 1.317 (G-Rg1), and 0.037 (M-R2). The QAMS method met all validation criteria, and the quantitative results were highly consistent with those obtained by ESM, with %SMD values below 5.00% for all saponins analyzed. Conclusions: This study successfully developed and validated a QAMS method using G-Rb1 as a single reference standard for quantifying major saponins in Panax vietnamensis. The method provides accurate, reliable, and cost-effective results comparable to the traditional external standard method. QAMS has been increasingly adopted in advanced pharmacopoeias worldwide, reflecting a global trend toward more efficient and practical analytical methods. By introducing this modern approach for Vietnamese ginseng, the study reduces dependence on multiple reference standards, lowers testing costs, and provides a reliable tool for routine analysis and standardization.